Preemptive Analgesia in Thumb Basal Joint Arthroplasty: Immediate Postoperative Pain with Preincision versus Postincision Local Anesthesia - Labrum, Joseph T., IV; Ilyas, Asif M. (Journal of Hand and Microsurgery, 2017)
Purpose Currently no guidelines exist for the timing of the injection of anesthetics in surgeries performed under general anesthesia to minimize postoperative pain. To better understand the role of timing of the injection of local anesthesia in hand surgery performed under general anesthesia, we evaluated the effect of pre- versus postincisional local analgesic injection on immediate postoperative pain experience. We hypothesize that the preincisional (preemptive) injection will result in decreased immediate postoperative pain experience and analgesic use when compared with postincisional injection.Methods Consecutive cases of thumb basal joint arthroplasty performed over a 4-year period were retrospectively reviewed. During the first half of the study period, the surgical site was infiltrated with 0.5% bupivacaine at the completion of surgery following closure. During the second half of the study period, the surgical site was infiltrated with 0.5% bupivacaine prior to skin incision. Data collected included patient demographics, immediate postoperative recovery room (PACU) pain scores, and postoperative opioid consumption in morphine equivalents.Results Two-tailed t-test identified no significant difference between the pre- and postincision cohorts relative to PACU entrance pain scores and time spent in the PACU. PACU exit pain scores were significantly lower in the preincision cohort. The mean PACU pain score was also significantly lower in the preincision cohort. PACU opioid consumption, converted into morphine equivalents, was found to be 211 mg in the preincision versus 299 mg in the postincision cohort.Conclusion The preincisional (preemptive) injection of local anesthesia was found to result in lower pain scores during and upon exit of the PACU as compared with the postclosure group. In addition, the preincision cohort also trended toward lower opioid consumption while in the PACU. Consideration should be given to the routine use of preincision injection of local anesthesia to maximize pain relief in a multimodal pain strategy in hand surgical patients.Level of Evidence Therapeutic level III.
Keywords: preemptive; analgesia; BJA; pre-incision; anesthetic; bupivacaine; Marcaine